Great powers and regional order [ the United States and the Persian Gulf - Kaim, Markus , 1968- (US foreign policy and conflict in the Islamic world series, 2008)
Explores the manifestations of US power in the Persian Gulf and the limits of American influence. This volume offers an exploration of both US domestic politics as it impacts policy toward the region, as well as the role played by that region on regional order and stability